Complete Denture Video - Rosalia Rey; Monica A. Fernandez; Maria Lucia Aguilar; Luis J. Rueda (Association of American Medical Colleges, 2012)
Abstract Although there are manuals that describe each patient visit needed for the fabrication of a complete partial denture, this video resource demonstrates the clinical techniques to be performed with a patient at each appointment. The six visits are (1) primary impressions, (2) final impressions, (3) maxillomandibular relations, (4) try-in appointment, (5) insertion, and (6) adjustments. Clinical concepts covered include the handling of dental biomaterials, armamentarium, and recognition of anatomic landmarks essential to achieving preliminary and final impressions. The video provides students with a visit-by-visit review of the clinical criteria to be achieved with the patient. The importance of border molding, trimming of the custom tray, how to take a maxillomandibular relation record, vertical dimension at rest and vertical dimension of occlusion measures, and how to do a clinical remount are emphasized. Additionally, this video models essential communication between the patient and provider, as well as organizational skills necessary for each patient visit. The video can be used by faculty in class to demonstrate clinical procedures in fabricating a complete denture and can also be used independently for student review prior to clinical treatment of patients to help students as they build clinical competencies.